مصادر ضغوط العمل وسبل مواجهتها لدى الممرضات العاملات في مستشفى القدموس الوطني - صالح, ليندا (Latakia University Journal -Medical Sciences Series, 2017)
تعرف ضغوط العمل بالقاتل الصامت ومهنة التمريض تتوافر فيها مصادر عديدة للضغوط. تهدف هذه الدراسة للتعرف على مصادر ضغوط العمل وسبل مواجهتها لدى الممرضات العاملات في مستشفى القدموس الوطني. تكونت عينة الدراسة من 50% من ممرضات مستشفى القدموس( 90 ممرضة), تم اختيارهم بشكل عشوائي, واستخدم الباحث استبانة قام بتطويرها من خلال الاطار النظري والدراسات السابقة. أظهرت نتائج الدراسة أن الدرجة الكلية لمصادر ضغوط العمل لدى الممرضات كانت متوسطة حيث وصلت النسبة المئوية للاستجابة الى ( 62.8%), وكان مجال مصادر الضغوط النفسية والاجتماعية في المرتبة الأولى, والضغوط الادارية والفنية في المرتبة الثانية, وفي المرتبة الثالثة الضغوط المتعلقة ببيئة العمل, بينما كان مجال مصادر الضغوط الشخصية في المرتبة الأخيرة. كما أظهرت الدراسة أن السبل الايجابية في مواجهة الضغوط كالحصول على النصح والارشاد ومناقشة المشكلات وتحديد أولويات العمل كانت أكثر استخداما لدى أفراد عينة الدراسة من السبل السلبية كتغيير العمل و اللجوء للأدوية. وبناءا على النتائج خلصت الدراسة الى العديد من التوصيات من أهمها اعادة النظر في الرواتب والحوافز, وايجاد وصف وظيفي للممرض, وتحسين ظروف العمل .Job stress is defending as silent killer, nursing profession is stressful job. The aim of this study is to identify job stress sources and coping styles among nurses working in al-kadmous governmental hospitals, a sample consisted of (50%) of nurses (90 nurse) were randomly selected for this study, the questionnaire was developed by the researcher based on references and literature review. the result show that the total degree of general average of job stress sources was moderate, the percentage (62.8%) of the psychosocial stress domain was in the first degree, administration stress domain in the second degree, the third degree work place environment related stress, and domain of personality stress came last in order. Also, Shows the study that positive styles of coping stress such as access to advice and guidance, problems discussion, and identify priorities of work were most use among study sample from negative styles such as changing work, and the use of drug. Based upon the results. To conclude, the study has proposed the following recommendation: there is a need for raising salaries and incentives, implementation of a job description plan, improvement of working conditions.